Encyclopedia of community from the village to the virtual world - Christensen, Karen 1957-.; Levinson, David 1947-.; Gale Group (Thousand Oaks, Calif. Sage Publications, 2003)
"This encyclopedia is a welcome exploration of the great variety of social networks that human beings create and participate in. Interdisciplinary in scope, the set includes contributions from some of the foremost scholars studying community today. Appendixes include an extensive bibliography, a collection of resources guides, an annotated guide to "Community in Popular Culture," and "Libraries Build Community," a guide for librarians."--"The Top 20 Reference Titles of the Year," American Libraries, May 2004.
"Whether the reader is a student, researcher, or professional in the field of psychology, sociology, or even economics, this four-volume work will provide the necessary definitions of community beyond traditional views."--GVRL description.
List of entries -- List of sidebars -- Reader's guide -- Contributors -- Introduction -- Acknowledgements -- About the editors -- Volume I: A-D -- Volume II: E-L -- Volume III: M-S -- Volume IV: T-Z -- Appendix 1: Resource guides -- Appendix 2: Libraries build community -- Appendix 3: Community in popular culture -- Appendix 4: Master bibliography of community -- Index.
Electronic reproduction.
Keywords: Communities -- Encyclopedias; Electronic books